2008
DOI: 10.1021/ic702310t
|View full text |Cite
|
Sign up to set email alerts
|

Heteropolynuclear Complexes of 3,5-Dimethylpyrazolate [Pt2M4(Me2pz)8] (M = Ag, Cu). Highly Luminescent Character of the Triplet Excited State Based on Mixed-Metal Cores

Abstract: The platinum dimer and heteropolynuclear platinum complexes of 3,5-dimethylpyrazolate, [Pt2M4(mu-Me2pz)8] [M = H (1), Ag (2), Cu (3)], were synthesized and structurally characterized. They exhibit yellow, sky-blue, and orange luminescence, respectively, in the solid state. The absorption bands of 2 and 3 are mainly assigned to the combination of the metal-metal-to-ligand charge-transfer and [Pt2 --> Pt2M4] transitions by the time-dependent density functional theory (DFT) method. DFT calculations also indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…[12] The successful control of emission energies, that is, the successful control of the nature of the singly occupied molecular orbitals (SOMOs), by the change of the incorporated coinage metal ions, which have different orbital energies corresponding to the nature of them, was attributed to the fact that the emissive states of [Pt 2 M 4 A C H T U N G T R E N N U N G (m-Me 2 pz) 8 ] (M= Cu (1), Ag (2)) are 3 (Cu(d)!Pt 2 Cu 4 ) and 3 (Pt 2 !Pt 2 Ag 4 ), respectively. The emission was assigned to the transition from the in-phase combination of 6p(Pt) and 4p (Cu) to the dp(Cu) orbital localized on one of the four Cu atoms for the Pt À Cu complex and that from the in-phase combination of 6p(Pt) and 5p(Ag) to the dd(Pt) non-bonding orbital for the Pt À Ag complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12] The successful control of emission energies, that is, the successful control of the nature of the singly occupied molecular orbitals (SOMOs), by the change of the incorporated coinage metal ions, which have different orbital energies corresponding to the nature of them, was attributed to the fact that the emissive states of [Pt 2 M 4 A C H T U N G T R E N N U N G (m-Me 2 pz) 8 ] (M= Cu (1), Ag (2)) are 3 (Cu(d)!Pt 2 Cu 4 ) and 3 (Pt 2 !Pt 2 Ag 4 ), respectively. The emission was assigned to the transition from the in-phase combination of 6p(Pt) and 4p (Cu) to the dp(Cu) orbital localized on one of the four Cu atoms for the Pt À Cu complex and that from the in-phase combination of 6p(Pt) and 5p(Ag) to the dd(Pt) non-bonding orbital for the Pt À Ag complex.…”
mentioning
confidence: 99%
“…In this paper, we will focus on a synergetic effect of the three transition elements.We have recently reported that the 3,5-dimethylpyrazolate (Me 2 pz)-bridged Pt-Ag complex, [Pt 2 Ag 4 A C H T U N G T R E N N U N G (m-Me 2 pz) 8 ], exhibits bright sky-blue luminescence in the solid state upon exposure to UV radiation (F = 0.85), and that the replacement of Ag I ion with Cu I ion in the hexanuclear complex reduces the emission energy to exhibit orange luminescence. [12] The successful control of emission energies, that is, the successful control of the nature of the singly occupied molecular orbitals (SOMOs), by the change of the incorporated coinage metal ions, which have different orbital energies corresponding to the nature of them, was attributed to the fact that the emissive states of [Pt 2 M 4 A C H T U N G T R E N N U N G (m-Me 2 pz) 8 ] (M= Cu (1), Ag (2)) are 3 (Cu(d)!Pt 2 Cu 4 ) and 3 (Pt 2 !Pt 2 Ag 4 ), respectively. The emission was assigned to the transition from the in-phase combination of 6p(Pt) and 4p(Cu) to the dp(Cu) orbital localized on one of the four Cu atoms for the Pt À Cu complex and that from the in-phase combination of 6p(Pt) and 5p(Ag) to the dd(Pt) non-bonding orbital for the Pt À Ag complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrazole or pyrazole derivatives have been widely employed in polypyrazolylborates to stabilize a variety of organometallic and coordination compounds,19,20 Up to now, a variety of complexes containing pyrazole (Hpz) ligands have been synthesized and employed in coordination chemistry or organometallic chemistry 21–23. Many complexes with simple pyrazole both in terminal as well as in bridging mode are also available 24–26.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Naota and co‐workers reported highly phosphorescent crystals of vaulted trans ‐bis(salicylaldiminato)platinum(II) complexes; one of the complexes showed intense emission ( Φ PL = 0.38) in the solid state at 298 K 8. Umakoshi and co‐workers presented a 3,5‐dimethylpyrazolate (Me 2 pz)‐bridged Pt 2 Ag 4 complex, [Pt 2 Ag 4 (Me 2 pz)], that exhibited bright‐blue luminescence in the solid state ( λ em = 497 nm, Φ PL = 0.85) 9. Additionally, Wang and co‐workers reported that triarylboron‐functionalized Pt II complexes bearing N‐heterocyclic carbene ligands displayed highly efficient blue or blue‐green phosphorescence in solution ( Φ PL = 0.41–0.87) and in poly(methyl methacrylate) films ( Φ PL = 0.86–0.90) 10…”
Section: Introductionmentioning
confidence: 99%